Genome-wide patterns of segregation and linkage disequilibrium: the construction of a linkage genetic map of the poplar rust fungus Melampsora larici-populina - Pernaci, Michaël; De Mita, Stéphane; Andrieux, Axelle; Pétrowski, Jérémy; Halkett, Fabien; Duplessis, Sébastien; Frey, Pascal (Frontiers in Plant Science, 2014)
The poplar rust fungus Melampsora larici-populina causes significant yield reduction and severe economic losses in commercial poplar plantations. After several decades of breeding for qualitative resistance and subsequent breakdown of the released resistance genes, breeders now focus on quantitative resistance, perceived to be more durable. But quantitative resistance also can be challenged by an increase of aggressiveness in the pathogen. Thus it is of primary importance to better understand the genetic architecture of aggressiveness traits. To this aim, our goal is to build a genetic linkage map for M. larici-populina in order to map quantitative trait loci related to aggressiveness. First, a large progeny of M. larici-populina was generated through selfing of the reference strain 98AG31 (which genome sequence is available) on larch plants, the alternate host of the poplar rust fungus. The progeny’s meiotic origin was validated through a segregation analysis of 115 offspring with 14 polymorphic microsatellite markers, of which 12 segregated in the expected 1:2:1 Mendelian ratio. A microsatellite-based linkage disequilibrium analysis allowed us to identify one potential linkage group comprising two scaffolds. The whole genome of a subset of 47 offspring was resequenced using the Illumina HiSeq 2000 technology at a mean sequencing depth of 6X. The reads were mapped onto the reference genome of the parental strain and 144,566 SNPs were identified across the genome. Analysis of distribution and polymorphism of the SNPs along the genome led to the identification of 2580 recombination blocks. A second linkage disequilibrium analysis, using the recombination blocks as markers, allowed us to group 81 scaffolds into 23 potential linkage groups. These preliminary results showed that a high-density linkage map could be constructed by using high-quality SNPs based on low-coverage resequencing of a larger number of M. larici-populina offspring.